Shadows of WWII - Sato, Yumiko (Voices: A World Forum for Music Therapy, 2010)
On my initial visit with Shen I discovered that he grew up in China under the Japanese occupation during WWII. How would my nationality affect our therapeutic relationship? As a Japanese music therapist working at hospice in America the shadow of WWII is something I can not avoid. Neither can my patients. For those who lived through the war meeting someone from Japan could bring back powerful emotions, especially when they’re facing their final journeys. This is a story of patients for whom both music and my nationality opened the door to unexpected experiences. All identifying information has been changed to protect people’s confidentiality.